1994
DOI: 10.1111/j.1399-3054.1994.tb05339.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spinach leaf α‐l‐arabinofuranosidases and β‐galactosidases and their synergistic action on an endogenous arabinogalactan‐protein

Abstract: Two β‐galaclosidases (β‐Galase‐I and ‐II, EC 3.2.1.23) and two α‐l‐arabinofuranosidases (α‐l‐Arafase‐I and ‐II. EC 3.2.1.55). were purified from mesophyll tissues of spinach (Spinacia oleracea L.), using chromatography on DEAE‐cellulose, lactose‐conjugated Sepharose CL‐4B, and Sephadex G‐100, or on hydroxylapatite and Sephadex G‐150. The apparent molecular mass (Mr) of β‐Galase‐I and ‐II, respectively, were estimated to be 38 000 and 58 000 on SDS‐PAGE and 64 000 and 60 000 on gel‐permeation chromatography, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…These enzymes can be classified into the second class of b-galactosidases, the b-galactosidase/exo-b-(1/3)(1/6)-galactanases. However, we cannot rule out the possibility that this second group of b-galactosidases participates in the degradation of both pectic b-(1/4)-galactan and the carbohydrate moieties of AGPs, because a b-galactosidase specimen (b-Gal II) purified from spinach leaves shows a broad substrate specificity, acting not only on b-(1/3)-and b-(1/6)-galactooligosaccharides but also weakly on b-(1/4)-galactooligosaccharides (Hirano et al, 1994). Further studies are required to clarify the functional differences of the second class of b-galactosidases from b-galactosidase/exo-b-(1/4)-galactanases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes can be classified into the second class of b-galactosidases, the b-galactosidase/exo-b-(1/3)(1/6)-galactanases. However, we cannot rule out the possibility that this second group of b-galactosidases participates in the degradation of both pectic b-(1/4)-galactan and the carbohydrate moieties of AGPs, because a b-galactosidase specimen (b-Gal II) purified from spinach leaves shows a broad substrate specificity, acting not only on b-(1/3)-and b-(1/6)-galactooligosaccharides but also weakly on b-(1/4)-galactooligosaccharides (Hirano et al, 1994). Further studies are required to clarify the functional differences of the second class of b-galactosidases from b-galactosidase/exo-b-(1/4)-galactanases.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is that the structure of pectic b-(1/4)-galactan is regulated spatially during the development of plant tissues, and pectin thus plays an important role in the architecture of the cell wall and intercellular attachment (McCartney et al, 2000;Sørensen et al, 2000). On the other hand, we have previously shown that b-galactosidase specimens isolated from radish seeds and spinach leaves (spinach b-Gal I) hydrolyze specifically b-(1/3)-and b-(1/6)-galactooligosaccharides besides PNP-b-Gal, and are thereby able to degrade the b-(1/3)(1/6)-galactan backbones of AGPs, but not pectic b-(1/4)-galactan (Sekimata et al, 1989;Hirano et al, 1994). These enzymes can be classified into the second class of b-galactosidases, the b-galactosidase/exo-b-(1/3)(1/6)-galactanases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the enzyme possesses bifunctional activity as a-L-arafase/b-xylosidase as an enzymatic property. Bifunctional activity has been reported in plant a-L-arafases purified from radish (Raphanus sativus) seeds (Hata et al, 1992) and spinach (Spinacia oleracea) leaf (Hirano et al, 1994) besides barley (Lee , 2003). It is not clear whether these a-L-arafases belong to GH family 3 or not; however, it may be reasonable that several b-xylosidases grouped family 3 were called a-L-arafase rather than b-xylosidase.…”
Section: Characterization Of A-l-arabinofuranosidasementioning
confidence: 99%
“…βgal is widely distributed and assessed in many creatures, such as insects (Seddigh and Bandani, 2012), and different plant tissues, like leaves (Hirano et al, 1994), seedlings (Li et al, 2001), hypocotyls (Kotake et al, 2005), and meristem zones of roots, cotyledons, vascular tissues, trichomes, and pollens (Hruba et al, 2005;Wu and Liu, 2006). The enzyme has been implicated in a number of biological processes, including plant growth and fruit ripening.…”
Section: Introductionmentioning
confidence: 99%